Reliability Analysis for Dynamic Behaviour, Stiffness, and Strength of Existing Steel Truss Bridge BH77 - Dimas Aryo Suseno; Pariatmono Pariatmono (Eduvest - Journal of Universal Studies, 2024)
Railway bridges are old, especially on the Sumatra island and according to earthquake map on 2017 version show an increased risk, it is necessary to analyze the reliability of dynamic behaviour to extend the bridge life and damage can be detected early. The bridge reliability was assessed in terms of natural frequency, deflection, and internal force . The study was conducted on the BH77 Railway Bridge in Tegineneng-Lampung, a through truss type. Reliability analysis with a non-deterministic approach, using the probability concept, variability used is the dimensions of steel profiles based on fabrication drawings and field measurements. The research uses secondary data, one of which is measurement of the circumference of the steel cross section, that influenced by the paint layer, where the paint thickness sample to correct and obtain the actual dimensions. Dynamic behaviour analysis, consisting of modal analysis, Fast Fourier Transform, time history, and First Order Reliabilty Method. The analysis results showed the effect of steel dimension correction compared to the fabrication drawings did not have a significant effect on the changes in the values of natural frequencies, mode shapes, deflections, and internal forces. The reliability of the dynamic behaviour obtained was 99% at all reviews. Which indicates that the bridge is safe against potential resonance, the bridge stiffness is still high, and the axial+moment capacity is still sufficient against static & earthquake loads, as well as good bridge maintenance. The largest deflection point as a reference for placing strain and vibration gauges on structural health monitoring systems.